Shi'ism in Turkey: A Comparison of the Alevis and the Ja'faris - (:unkn) unknown (ISLAMIC COLL ADV STUD-ICAS, 2010)
Both Alevism and Ja'farism are religious minority groups in Turkey which are sometimes conflated due to their reverence of some common figures, such as 'Ali ibn Abi Talib and his descendants. However, despite the similarities between the two groups, there are many differences in the belief systems and sociocultural structures. This article highlights some of the key similarities and differences between Alevism and Jalarism.
Keywords: Alevism; Ja'farism; Twelver (Ithna 'Ashari); Turkey